2020
DOI: 10.24874/ti.847.02.20.06
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Wear Behavioural Response of Al-Limestone Slurry Composite Using Taguchi Orthogonal Array

Abstract: Limestone slurry powder (LSP) is one of the solid wastes generated from stone processing industry, used as reinforcing agent replaced conventional ceramic compounds in Aluminum Metal Matrix composites (AMCs) to increase mechanical and tribological properties. In this work aluminum (Al)-magnesium ( Mg)-silicon (Si) alloy is strengthened with addition of LSP to determining the tribological performance of Al-LSP composites are composed with 4, 8, 12 and 16 % weight ratio, and prepared via double stir casting. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
(22 reference statements)
0
3
0
Order By: Relevance
“…Grey-fuzzy reasoning grade (GFRG) has been shown to increase the performance of wear behaviour features in the tribological process, as shown by experimental data. Lokanadham et al, (2020) [22] stated that a solid waste called LSP is being employed as a reinforcing material. Al-LSP composites are made with 4, 8, 12, and 16% weight ratios, and are manufactured by double stir casting, to determine the tribological performance of aluminium (Al), magnesium (Mg), and silicon (Si) alloy to improve the mechanical and tribological characteristics of "Aluminum Metal Matrix Composites (AMCs)".…”
Section: Figure 1 Schematic Descriptions Of Adhesive Andmentioning
confidence: 99%
“…Grey-fuzzy reasoning grade (GFRG) has been shown to increase the performance of wear behaviour features in the tribological process, as shown by experimental data. Lokanadham et al, (2020) [22] stated that a solid waste called LSP is being employed as a reinforcing material. Al-LSP composites are made with 4, 8, 12, and 16% weight ratios, and are manufactured by double stir casting, to determine the tribological performance of aluminium (Al), magnesium (Mg), and silicon (Si) alloy to improve the mechanical and tribological characteristics of "Aluminum Metal Matrix Composites (AMCs)".…”
Section: Figure 1 Schematic Descriptions Of Adhesive Andmentioning
confidence: 99%
“…The obtained results suggested that either reinforcement with sole granite (2 wt %) or with a combination of granite and graphite (4 and 2 wt %, respectively) contribute to a decrease in the value of COF as compared to neat A356 alloy. In another study, a limestone slurry powder (also a waste from the stone cutting industry) was used to reinforce the aluminum-magnesium-silicon alloy matrix [ 116 ]. The authors observed a decrease in COFs for samples reinforced with the limestone slurry powder, with the optimal weight percentage of waste being 12% (the maximal studied content of waste was 16 wt %).…”
Section: Industrial Waste Materialsmentioning
confidence: 99%
“…The LSP (1.7–2.9 g/cm 3 ) is lower in density than aluminium (2.7–2.9 g/cm 3 ) as well as classic fillers (SiC: 3.21 g/cm 3 and Al 2 O 3 : 3.95 g/cm 3 ). A detailed study on tribological performance of Al-LSP composites with varying weight percentage has been studied elsewhere (Lokanadham and Subbaiah, 2020). The previous work revealed that, Al-LSP (LSP 12% by weight) composite exhibited better mechanical properties and tribological performance in comparison with other composites.…”
Section: Introductionmentioning
confidence: 99%